In pursuit of a sustainable traffic and transportation system: a case study of Kolkata. (2017) - Bandyopadhayay, Asit; Banerjee, Ashim
Kolkata is one of the most important cities of India. The gradual growth in terms of population and commerce increased the demand for transportation. The attempts to improve the transportation system through marginal investment in the development of infrastructure have failed to provide any respite. The impasse location of Kolkata port greatly constraints the transportation system of the city. Low road space availability and sparse railway infrastructure in the inner city adds to the transportation woes. Various government and non-government organisations are engaged in the process of mass transportation but their isolated efforts are unable to resolve the problem. In this paper the authors have made an effort to discuss the prevailing traffic and transportation scenario of the city and recommended solution in the form of analytical, fact-based discussion to reduce the level of traffic congestion in the city and in doing so cooperation of all sectors (including government) and people are urgently required.